Romancing Masculinities in Utsana Phleungtham's The Story of Jan Darra: A Thai Literature - Desca Angelianawati; Darsono Darsono (British : Jurnal Bahasa dan Sastra Inggris, 2020)
The portrayal of male masculinities varies from time to time following the engulfment of gender studies. It is seen from the significant increase of the discussion related to male and masculinities. Furthermore, discussions of masculinity are linked with how a particular culture perceive masculinity. In several Thai folktales and so-considered classic literature like the Legendary Tale of Krai Thong and the Legend of Phra Chao Sua, the heroes and the warriors present themselves as masculine. Their manly assets including body and gesture have become the exploitation of the story whilst being the model of masculinity. Utsana Phleungtham’s two main male characters in the novel the Story of Jan Dara is without exception. Those heroes of the story portray male masculinities through their existence and domination. Undertaking the library studies, this article illustrates how male masculinities are depicted and why it is manifested though those characters. The findings show that the male masculinities are presented vividly in order to maintain the rooted masculine domination.